Game-Based Learning Innovations in Physical Education: A Literature Review - Asep Sahrul Gunawan; Teguh Priyanto; Airil Fitra Alhakiki; Ari Jayadi Putra (Kampus Akademik Publiser, 2026)
Game-Based Learning (GBL) is an increasingly developing learning innovation in physical education; however, research on its implementation remains scattered across various contexts, research designs, and forms of innovation, thus not yet providing a comprehensive overview of the field's development. This study aims to analyze the development of Game-Based Learning innovations in physical education through a literature review of research published between 2022 and 2026. The study utilized the Narrative Literature Review method by analyzing 25 scientific articles selected based on inclusion and exclusion criteria. Data were analyzed using thematic analysis to identify research characteristics, main themes, and the direction of research development. The review results indicate that GBL innovations have evolved from conventional games toward gamification, Teaching Games for Understanding (TGfU), exergames, digital games, and technology-based learning. Research themes are dominated by learning motivation, student engagement, learning outcomes, motor skills, physical fitness, and social interaction. This study concludes that GBL has strong potential to support more innovative and student-centered physical education learning and provides an overview of research trends and developmental opportunities that can serve as a reference for future research and learning practices.